Fintech in a flash financial technology made easy - Rubini, Agustín (De Gruyter, 2024)
Master the dynamic world of financial technology with Fintech in a Flash, Fourth Edition - your definitive guide to managing and optimizing your online finances and staying ahead of the curve in an era where digital finance is reshaping our lives. As global investment in fintech soars and startups reach new heights, understanding this sector is more crucial than ever. This comprehensive manual demystifies the rapidly evolving fintech landscape, transforming complex concepts into digestible insights. Whether it's exploring online payments, diving into challenger banks, or dissecting insurtech and wealthtech, this book has you covered. Here's what sets it apart: Concise yet thorough explanations of the 14 fundamental fintech pillars. Projections into the future of fintech, preparing you for what's next. A deep dive into global fintech hotspots and the game-changing 'Unicorns.' A handpicked selection of emerging fintech stars to watch. Authored by Agustin Rubini, a celebrated fintech and AI expert, this book is an indispensable resource. Whether you're an entrepreneur, a professional in banking and finance, a consultant, or simply a fintech enthusiast, Fintech in a Flash provides you the knowledge to navigate and excel in the fintech revolution